2019
DOI: 10.1364/oe.27.019635
|View full text |Cite
|
Sign up to set email alerts
|

On the realization of across wavy water-air-interface diffuse-line-of-sight communication based on an ultraviolet emitter

Abstract: We experimentally demonstrated high-speed diffuse line-of-sight optical wireless communication across a wavy water-air-interface. The testbed channel was evaluated, in terms of data rate, coverage and robustness to the dynamic wave movement, based on the performance of different modulation schemes, including non-return-to-zero on-off keying (NRZ-OOK) and quadrature amplitude modulation (QAM)-orthogonal frequency division multiplexing (OFDM). Under the emulated calm water condition, 8-QAM-OFDM offers a data rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…To simultaneously maximize the achievable data rates and enhance the resiliency to channel uncertainty, amplitude-modulated orthogonal frequencydivision multiplexing (QAM-OFDM) modulated signals were utilized in the system. Furthermore, our previous studies [10] indicated that the low signal-to-noise ratio (SNR) requirements and the ability to mitigate intersymbol interference (ISI) can be achieved using lower order QAM-OFDM modulation schemes based on three key performance matrices: data rates, robustness against waves, and communication coverage. In this system, the QAM-OFDM modulations with a high spectral efficiency were generated offline in MATLAB and uploaded to an arbitrary waveform generator (AWG, Tektronix AWG70002A).…”
Section: Design Of Free-space Laboratory Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…To simultaneously maximize the achievable data rates and enhance the resiliency to channel uncertainty, amplitude-modulated orthogonal frequencydivision multiplexing (QAM-OFDM) modulated signals were utilized in the system. Furthermore, our previous studies [10] indicated that the low signal-to-noise ratio (SNR) requirements and the ability to mitigate intersymbol interference (ISI) can be achieved using lower order QAM-OFDM modulation schemes based on three key performance matrices: data rates, robustness against waves, and communication coverage. In this system, the QAM-OFDM modulations with a high spectral efficiency were generated offline in MATLAB and uploaded to an arbitrary waveform generator (AWG, Tektronix AWG70002A).…”
Section: Design Of Free-space Laboratory Systemmentioning
confidence: 99%
“…Conventional acoustic waves [17] mostly reflect off the water surface without transmitting, whereas RF waves rapidly decay in water because of their high attenuation [18]. State-of-the-art workarounds for this problem have been proposed in [10] using relay assets [19], surfacing, integrated acoustic RF wireless systems (translational acoustic RF (TARF) communications, MIT, 2019) [20], and line-of-sight (LOS) optical links [7], [21], [22]. However, relay and surfacing involve large signal delays and security concerns, respectively, while TARF suffers from low data rates (400 bit/s).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A feedback-assisted orbital angular momentum-based W2A-OWC link was established in [15], using a 520 nm green light laser diode. In [16], an ultraviolet communication system was demonstrated across the wavy W2A interface. A W2A laser communication system was realized in [17], which achieves a data rate of 44 Mb/s over a 2.3-m underwater and 3.5-m air link.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with an SDM-based FSO-UWOC integrated system, this proposed WDM-based FSO-UWOC integrated system is notable for its simplicity and practicality. Sun et al achieved a diffuse-line-of-sight communication across a wavy water-air interface based on NRZ on-off keying (OOK) and quadrature amplitude modulation (QAM)-orthogonal frequency-division multiplexing (OFDM) modulations [23]. However, the modulation can be enhanced and simplified by adopting PAM4 modulation.…”
Section: Introductionmentioning
confidence: 99%